Molecular Regulation of Toll-like Receptors in Asthma and COPD - Zuo, Li; Lucas, Kurt; Fortuna, Christopher A.; Chuang, Chia-Chen; Best, Thomas M. (Frontiers in Physiology, 2015)
Asthma and chronic obstructive pulmonary disease (COPD) have both been historically associated with significant morbidity and financial burden. These diseases can be induced by several exogenous factors, such as pathogen-associated molecular patterns (PAMPs) (e.g., allergens and microbes). Endogenous factors, including reactive oxygen species and damage-associated molecular patterns (DAMPs) recognized by toll-like receptors (TLRs), can also result in airway inflammation. Asthma is characterized by the dominant presence of eosinophils, mast cells, and clusters of differentiation (CD)4+ T cells in the airways, while COPD typically results in the excessive formation of neutrophils, macrophages, and CD8+ T cells in the airways. In both asthma and COPD, in the respiratory tract, TLRs are the primary proteins of interest associated with the innate and adaptive immune responses; hence, multiple treatment options targeting TLRs are being explored in an effort to reduce the severity of the symptoms of these disorders. TLR-mediated pathways for both COPD and asthma have their similarities and differences with regards to cell types and the pro-inflammatory cytotoxins present in the airway. Because of the complex TLR cascade, a variety of treatments have been used to minimize airway hypersensitivity and promote bronchodilation. Although unsuccessful at completely alleviating COPD and severe asthmatic symptoms, new studies are focused on possible targets within the TLR cascade to ameliorate airway inflammation.